Konsep Pendidikan Menurut Al- Ghazali dan Al-Farabi (Studi Komparasi Pemikiran) - Agung Setiyawan (Tarbawiyah Jurnal Ilmiah Pendidikan, 2016)
The concept of education is always interesting to discuss. Many figures have been peeled from both Muslims and non-Muslims. Al-Ghazali and Al-Farabi are the second Muslim leaders who have great attention to education. Thought both are interesting to compare because it has almost the same background in philosophy so that the approach in this study used acomparative study with the object of the discussion focused on the two men thought about the concept of education. The result showed that education in the thinking of al-Ghazali should lead to the realization of religious and moral character, with the emphasis on the acquisition of virtue and taqarrub to God and not to seek a high position or gain magnificence of the world while according to Al-Farabi, education as a means for get a set of values, knowledge, and practical skills for individuals in certain periods and cultures. The end goal, guiding individuals towards perfection.